The Notion of Activity in Chemistry - Burgot, Jean-Louis (Springer International Publishing : Imprint: Springer, 2017)
This book provides deep insight into the physical quantity known as chemical activity. The author probes deep into classical thermodynamics in Part I, and then into statistical thermodynamics in Part II, to provide the necessary background. The treatment has been streamlined by placing some background material in appendices. Chemical Activity is of interest not only to those in chemical thermodynamics, but also to chemical engineers working with mass transfer and its applications - for example, separation methods.- Resumé vydavatel